MODEL STRATEGI PENINGKATAN KUANTITAS MAHASISWA PROGRAM STUDI TEKNIK INDUSTRI UNISBANK SEMARANG - Eddi Indro Asmoro; Syafiq Hilmi MZ (Jurnal Ilmiah Dinamika Teknik, 2019)
The problem of quantity of new students from the year since its inception in 2002 until now in the Industrial Engineering Study Program is increasingly worrying. Identification of the root causes has been widely discussed by managers and management officials, but the reality is increasingly critical. Many methods have been carried out through various road promotion efforts but the results are still not significant. What is the root of the problem here?The proposed strategy model examines the problem from upstream to downstream with consideration of IFE and EFE, and is analyzed by SWOT from the perspective of SCM and SCI. Where the root of the problem is peeled off from the subjective perspective of the researcher based on the mapping of the Fish Bone Diagram.The expectation of this strategy model for increasing the quantity of Unisbank Industrial Engineering students in Semarang, even though it is still in the design phase of the strategy model.